Nevidno življenje odpadkov - Polajnar Horvat, Katarina; Podjed, Dan (ZRC SAZU, Založba ZRC, 2022)
The main purpose of this book is to show that waste does not disappear when we throw it away, but accumulates at an amazing rate, taking up more and more space on our planet. The authors, renowned experts in the fields of anthropology, ethnology and geography, describe local habits related to waste and present waste as an important factor in the global production and consumption network. Anyone reading the book will find it hard to ignore the pile of waste we are trying to sweep under the carpet.